Simulation and Development of Unified Power Flow Controller Using Multilevel Inverter - Mailah, Nashiren Farzilah (2010)
Heavily loaded transmission lines and the inability to control the amount and direction of power flows have became major concerns to the power utilities. Some of the solutions taken by the power utilities are by expanding the size of power system network in terms of building new transmission lines, using higher rating equipments and installing more generating units. The power utilities also have improved the transmission lines capability and better utilizing of existing power system networks. The power flows in the transmission lines in accordance to their series impedance, voltage magnitude at the sending end and receiving end, and phase angle between these two voltage ends. Electromechanically controlled devices have been used to control the power flow which is now steadily being replaced with static devices. The problem with these electromechanically controlled devices is sometimes they do not react fast enough especially during disturbances. Furthermore, they are subjected to wear and tear which requires regular monitoring and servicing. The advancement in power electronics devices, which provide faster response compared to the electromechanical ones and require less maintenance as they do not wear and tear easily has attracted great interest from the researchers. Among these power electronics devices, Unified Power Flow Controller (UPFC) has gained a lot of attention due to its ability to control, simultaneously or selectively, all the three of power system parameters i.e. line impedance, voltage magnitude and phase angle. In this work, UPFC’s simulation model has been designed and developed as a power system device to investigate the behaviour of the system under normal and abnormal conditions. A small-scale laboratory model has also been constructed to validate the findings obtained from the simulation model. To avoid high frequency components produced in Pulse Width Modulation (PWM), a 3-level Neutral Point Clamped (NPC) multilevel inverter has been proposed as the series inverter for the UPFC using Space Vector Modulation (SVM). The shunt inverter for UPFC is composed of a 6-pulse diode bridge rectifier and a line commutating thyristor bridge. A triggering circuit for the simulation model for the SSSC has been improved for Matlab/Simulink module. For the laboratory model, a switching circuit consists of PIC, optocouplers, IGBTs drivers and monostable multivibrators has been successfully constructed. The proposed 3-level NPC inverter has been shown to have a better feature in terms of Total Harmonics Distortion (THD) with a simulation value of 13.36% VLL and experimental value of 15.65% VLL. The THD value is lower compared to a similar work of 16.46%. The additional voltage phase shift, φ produced by the SSSC has been shown to affect the phase shift between the sending end voltage and receiving end voltage. As the line impedance and both voltages are usually constant, any variation in phase shift between the two voltages will affect the amount of power flows in the transmission lines and its direction. The THDs of the voltage and current of the SSSC when connected between two busbars have been determined and a good agreement between the simulation and laboratory results has been achieved. From the simulation, the THD value of line voltage is approximately 1.3% which is lower compared to other work of 2.49% and 3.58%. A comprehensive controllable UPFC using real power transfer algorithm and reactive power compensation algorithm has been successfully designed and constructed as a simulation model that is able to stabilize voltage with required power for fast changing loads.